Numerical investigation of droplet formation in T-junction microfluidic system with a semi-NACA-shaped squeezer - Ich Long Ngo; Dao, Van Nam; Chu, Thi-Xuan (Communications in Physics, 2025)
We present a numerical investigation of droplet formation in a T-junction microfluidic system with a semi-NACA-shaped squeezer. A two-dimensional numerical model is employed to simulate the droplet formation process using the Volume of Fluid method. The integration of this semi-NACA squeezer has a positive influence on the droplet formation dynamics under identical operating conditions. By varying the squeezer size, an inverse correlation is observed between squeezer size and droplet size. Additionally, the droplet formation process in the microfluidic T-junction device is highly dependent on the viscosity ratio, with droplet size decreasing as the viscosity ratio increases. These findings contribute to a better understanding of the droplet dynamic in T-junction devices, paving the way for new applications in microfluidic technology